PENGARUH PELAKSANAAN PROGRAM KESEJAHTERAAN PERAWAT DAN PROFESIONALISME KERJA TERHADAP KEPUASAN KERJA PERAWAT PADA RUMAH SAKIT HASAN SADIKIN BANDUNG - Ius Yuziana (Holistik Manajemen: Jurnal Manajemen, 2021)
The influence of implementation nurse prosperity program and the work profession and the job satisfaction of nurses at Bandung Hasan Sadikin Hospital, West Java, Master Program in Hospital management Langlang Buana University, 2021 This research aims to obtain information on the relationship between independent variables, namely, the implementation of the nurse prosperity program,and work professionalism with the dependent variable, namely the work frustrations of nurses Bandung Hasan Sadikin Hospital , West Java. The hypotheses tested are 1) there is a positive relationship between the implementation of the nurse prosperity program and the job satisfaction of nurses, 2) there is a positive relationship between work professionalism and job satisfaction of nurses, and 3) there is a positive relationship between the implementation of the nurse welfare program and the social work profession together. with the job satisfaction of nurses. This research was conducted at Hasan Sadikin Hospital Bandung West Java. for 3 months starting from Januari to Maret 2021. The research method used was a survey. The population in this study were all nurses at Bandung Hasan Sadikin Hospital , West Java, totaling 347 nurses. The sample was taken as many as 40 nurses from the existing population. The sample was selected by a simple random technique. The research instrument used was a quesionair in the form of answer choices. In this study, there are three main conclusions, namely (1) that the better the implementation of the nurse prosperity program for a nurse, the higher the job satisfaction of the nurse (2) that the higher the professionalism of a nurse, the higher the job satisfaction of the nurse (3) that the better the implementation of the nurse prosperity program for a nurse and the higher the professionalism of a nurse, the higher the job satisfaction of the nurse. Keypoint : Prosperity program nurse, work profession nurse, the job satisfaction nurse, and Bandung Hasan Sadikin Hospital.